FAKTOR-FAKTOR YANG MEMPENGARUHI INTERNET FINANCIAL REPORTING PADA PERUSAHAAN MANUFAKTUR - Veneishia Gricelda; Agustin Ekadjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this study was to analyze the effect of profitability, liquidity, leverage, firm size, and board size on internet financial reporting or IFR in manufacturing companies listed on the Indonesia Stock Exchange in 2019. This study used a purposive sampling method and obtained 90 samples. Data processing techniques use multiple linear regression analysis assisted by IBM SPSS Statistics 25 and Microsoft Excel programs. The results of this study indicate that profitability and firm size have significant positive effect on IFR, liquidity and board size have insignificant positive effect on IFR, while leverage has insignificant negative effect on IFR. The implication of this research is that it’s hoped thatcompanies can better utilize IFR to complete information for investors in determining their investment.